Muzakki's Perception Regarding Implementation Good Corporate Governance (GCG) Against Muzakki's Trust in OPZ - Mega Aulia Mulindra; Ira Novianty; Iwan Setiawan (Indonesian Journal of Economics and Management, 2023)
The management of zakat funds as an instrument for reducing poverty in Indonesia is still not optimal. The potential for zakat funds in Indonesia reaches 327 trillion, while the total funds raised by the Zakat Management Organization (OPZ) are still less than 4%, which is 12,429 trillion. This shows that muzakki's trust in OPZ is still low, one of the things that affects muzakki's trust is the implementation of Good Corporate Governance (GCG) carried out by zakat institutions. Muzakki can see the implementation of GCG through the accountability and transparency of the institution. This research was conducted by interviewing 100 muzakki who were then analyzed using the partial least squares (PLS) method. The conclusion from this study is that the implementation of GCG has a significant effect on trust.